Reflexões sobre o Ministério Público Estadual Brasileiro: um estudo sobre o papel do promotor de justiça na defesa do direito à educação de qualidade - Sá, Itanieli Rotondo (2014)
This is an analysis of the right to “quality education” as a key component in the consolidation of citizenship and democratic institutions and a catalyst for the expansion of other rights. The study looks into the applicability of the notion of “commitment” to public education, extending the term beyond the legal sphere, and, in light of education as a fundamental right, provides definitions for “quality education” and other key concepts. To do so, we surveyed the measures taken by Brazilian authorities to evaluate the quality of education, and the main arguments pitched against them. Reflecting the quality policies adopted by the State, these measures play an important role in the current social debate on educational demands. The quality concepts recognized by the Summits of the Americas, the Brazilian Government and representatives of State Public Ministries seated in the COPEDUC (Permanent Education Commission) were analyzed. School Augustinho Brandão, a public high school considered a national reference in quality education, was selected for a case study in order to identify and help disseminate the values and practices which have most contributed to the schoolʼs renown. The position of the Public Ministry in each state with regard to the issue of quality education was appraised based on data collected from members of COPEDUC, and the possibility of adopting a quality standard for the use of the Public Ministry was discussed. The contribution of the Public Ministry to education-related cases brought before the Supreme Federal Court and made available online was evaluated to determine the profile of the demand and the major arguments and principles adduced. Overall, our findings prompt a deeper analysis on the subject of “quality education” and on the role played by the Public Ministry in the defense and promotion of this concept and right. The study also provides subsidies for quality education policy makers at national level and highlights the importance of quality education to the exercise of citizenship in a democratic state.